Dilema Praktis Globalisme Neoliberal - Syeirazi, M. Kholid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2003)
The world currently witnesing both globalization and globalism. Globalization manifests in economic, political and cultural domain, provides prescriptive judgement on what to do and not to do. Praxis of neoliberal globalism is problematic because what readily avaiable is prescription rather than philosopical refferent. The world has increasingly more integrated, and nation state has been obsolete not because of the truth, but rather the prescriptive nature of the ideology.